FISIOTERAPI PASCA REKONSTRUKSI ANTERIOR CRUCIATE LIGAMENT DENGAN CONTINUOUS PASSIVE MOTION DAN TERAPI LATIHAN - Deo, Ignatius Lewas Nathan Kamuna (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Anterior Cruciate Ligament (ACL) reconstruction is a surgical procedure performed to replace a ruptured Ligament in the knee. Objective: aiming to restore joint stability and functional capacity following trauma such as sudden stops, twists, or jumps. This injury is commonly found in sports activities like football, basketball, and volleyball. Post-operative problems frequently encountered include pain, edema, limited range of motion, decreased muscle strength, and impaired functional activities such as transitioning from standing to squatting, squatting to standing, walking, and jumping. Physiotherapy plays a vital role in the rehabilitation process by reducing pain, improving muscle strength, restoring joint mobility, and enhancing functional performance. The physiotherapy modalities applied in this case include Continuous Passive Motion (CPM) to maintain passive joint movement, and Exercise Therapy, which is structured to accelerate recovery of muscle strength and postural control. Methode: This scientific paper is a case study, presenting a patient case and collecting data through the physiotherapy process. The modalities applied are Continuous Passive Motion and Exercise Therapy. Result: After four sessions of physiotherapy, the results showed an improvement in joint range of motion and muscle strength, a reduction in pain and edema, as well as an increase in the patient's functional ability. Conclusion: Continuous Passive Motion and Exercise Therapy given to the patient can help increase joint range of motion, muscle strength, and functional ability, as well as reduce pain and edema.